Atomistic mechanism of non-selective cation permeation in cyclic nucleotide-gated CNGA1 ion channel by molecular dynamics simulations - Haoran Liu; Johann Biedermann; Han Sun (Communications Biology)
Abstract Mammalian cyclic nucleotide-gated (CNG) ion channels play a fundamental role in signal transduction within the visual and olfactory sensory cells, converting external stimuli into electrical signals. Here, using large-scale atomistic molecular dynamics (MD) simulations of three different constructs under applied transmembrane voltages, we uncover the atomistic mechanism of monovalent cation permeation in the homotetrameric CNGA1 channel. Owing to the high plasticity and large dimensions of its selectivity filter (SF), monovalent cation binding within the SF of the CNGA1 channel is more dynamic and diffuse compared to that in potassium-selective and hyperpolarization-activated cyclic nucleotide-gated (HCN) channels. K+ and Na+ permeation in CNGA1 involves hydrated cations passing through the SF with strong occupancy at three regions. In addition, we proposed that the higher Na+ occupancy in the SF compare to K+ underlies the experimentally observed larger Na+ conductance. Our study provides atomistic insights into non-selective cation permeation mechanisms that are not accessible through static structural analysis alone.